2011
DOI: 10.1007/s00417-011-1726-5
|View full text |Cite
|
Sign up to set email alerts
|

Confocal laser-scanning microscopy allows differentiation between Fabry disease and amiodarone-induced keratopathy

Abstract: While Fabry-induced cornea verticillata and amiodarone keratopathy cannot be distinguished by conventional slit-lamp microscopy, CLSM allows the differentiation between both etiologies in the majority of patients. CLSM appears to reveal corneal changes prior to the detection of cornea verticillata on slit-lamp microscopy and may thus be helpful in the early diagnosis of Fabry disease. CLSM does not allow quantitative monitoring of corneal changes in Fabry patients under enzyme-replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 16 publications
1
24
0
2
Order By: Relevance
“…Cornea verticillata is the outcome of deposits of GB3 in the basal layer of the corneal epithelium 5. Cornea verticillata is visible through a slit lamp, and an in vivo confocal microscope study has shown that even when cornea verticillata is not visible through a slit lamp, there are intracellular inclusion bodies in the basal epithelial cells 6. A smaller number of patients have subtle lenticular deposits, which are known as Fabry cataracts 7.…”
Section: Introductionmentioning
confidence: 99%
“…Cornea verticillata is the outcome of deposits of GB3 in the basal layer of the corneal epithelium 5. Cornea verticillata is visible through a slit lamp, and an in vivo confocal microscope study has shown that even when cornea verticillata is not visible through a slit lamp, there are intracellular inclusion bodies in the basal epithelial cells 6. A smaller number of patients have subtle lenticular deposits, which are known as Fabry cataracts 7.…”
Section: Introductionmentioning
confidence: 99%
“…Yarıklı lamba biyomikroskopisi ile ayırıcı tanılarının yapılması mümkün değildir. 5,11,14,15 Cavanagh ve ark. 16 insan korneasının konfokal mikroskopi bulgularını ilk defa 1993 yılında yayınlamışlardır.…”
Section: Discussionunclassified
“…O zamandan beri amiodaron keratopatisinin daha ayrıntılı irdelenmesi ve olası diğer nedenlerden ayrımını yapabilecek bulguların tespit edilebilmesi için konfokal tarayıcı mikroskop kullanımı yaygınlaşmıştır. 10,11,[14][15][16] Konfokal mikroskopik incelemede; amiodaron keratopatisindeki depozitlerin Fabry hastalığındaki sifingolipid birikimlerinden farklı olarak daha yüksek yansıtıcılıkta olduğu, boyutlarının değişkenlik gösterdiği ve bunun yanı sıra daha az organize bir patern sergiledikleri bildirilmektedir. Ayrıca amiodaron keratopatisinde subepitelyal sinir tabakalarında ve endotel tabakasında da birikimler izlenebilirken Fabry hastalığında izlenmemektedir.…”
Section: Discussionunclassified
“…17 There is some evidence that in vivo confocal laser-scanning microscopy can detect differences between amiodarone-related corneal verticillata and FD. 20 Other rare ocular conditions can result in vortextype lesions at the level of …”
Section: Ocular Manifestations Of Fabry Disease Corneal Verticillatamentioning
confidence: 99%